An Assessment of the Relationship of Flash Retailing to Customer Engagement: Its Impact as a Marketing Strategy (American Journal of Economics and Business Innovation, 2025)
In a fast-moving region like Metro Manila, where trends can rise and fall rapidly, standing out as a brand becomes more challenging than ever. Pop-up stores, which are temporary retail shops designed to attract customers through time-limited shopping experiences, are an emerging tactic for marketing. One important aspect of this strategy is ephemerality, or the short-term nature of pop-up stores, which helps create urgency and plays a growing role in how businesses attract consumers. These stores help brands get noticed, connect better with customers, and spread awareness through both social media and real-life interactions. This research aims to define whether pop-up stores effectively engage customers and whether they can be a suitable strategy for startups and new product launches alike. The study was conducted in Metro Manila, Philippines, with 417 randomly selected respondents. Data were collected through survey questionnaires using a Likert scale to measure customers’ opinions on pop-up retailing. Simple random sampling was used to ensure unbiased responses. Factors that define customer engagement such as: brand recognition, brand appeal, word of mouth, customer satisfaction and personalized experiences, will be subtopics vitally used in identifying the relationship between the two main variables. The findings of this study will help businesses understand the role of pop-up stores in enhancing customer engagement and brand awareness. Additionally, it will offer insights into how the ephemeral nature of pop-up stores influences consumer behavior, generating a sense of exclusivity and excitement that traditional retail formats may not provide. The results may guide companies to improve their retail strategies and create a better experience for their customers.